Cr-Si SINTERED BODY
The Cr-Si sintered body, composed of chromium silicide and silicon with specific processing techniques, addresses the low strength and cracking issues of existing Cr-Si sintered bodies, achieving high strength and durability suitable for high-power sputtering applications.
Patent Information
- Application Number
- JP2025009355
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-06-11
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2039-11-11
AI Technical Summary
Existing Cr-Si sintered bodies used for thin film formation, particularly in semiconductors and solar cells, suffer from low strength and cracking issues during processing, limiting their effectiveness as sputtering targets.
A Cr-Si sintered body with a stoichiometric composition of chromium silicide (CrSi2) and silicon, produced using quenched alloy powders such as gas atomized powders, achieving a high density of 95% or more and an average particle size of 60 μm or less.
The resulting Cr-Si sintered body exhibits high bending strength of 100 MPa or more, reduced oxygen content, and improved durability, minimizing cracking during high-power sputtering and enhancing film formation productivity.
Smart Images

Figure 2025061607000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a Cr-Si sintered body for forming a thin film. [Background technology]
[0002] In recent years, silicides such as CrSi2 have been used as thin films in many places such as semiconductors and solar cells due to their characteristics. Sputtering methods are often used industrially to prepare thin films. However, compositions containing silicides such as CrSi2 generally have low strength and are prone to cracking during processing of the sputtering target and during discharge during film formation, making them difficult to use as sputtering targets. Therefore, in Patent Document 1, a sputtering target with a Cr and Si crystal phase is prepared by a thermal spraying method. However, the thermal spraying method does not provide sufficient strength in areas with a low Cr distribution, and the sputtering target prepared by the thermal spraying method using a powder of a silicide phase does not have high strength.
[0003] In addition, in Patent Document 2, a composition with a fine eutectic structure is produced by a melting method. However, the proportion of eutectic structure is small in the melting method, and high strength cannot be achieved in a composition with a large amount of primary crystals. Furthermore, when the size is increased, it becomes difficult to control the crystal structure due to differences in cooling speed, and unevenness in strength increases.
[0004] Furthermore, Patent Documents 3 and 4 make no mention of systems containing a large amount of silicide because the silicide phase is brittle. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-82314 A [Patent Document 2] Special Publication No. 2013-502368 [Patent Document 3] JP 2002-173765 A [Patent Document 4] JP 2003-167324 A Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a high-strength Cr-Si sintered body containing Cr (chromium) and silicon (Si). [Means for solving the problem]
[0007] The present inventors conducted extensive research into a manufacturing process for a Cr-Si sintered body having a stoichiometric composition of chromium silicide (CrSi2) and silicon (Si) and containing a specific amount or more of the CrSi2 phase. As a result, they discovered that a high-strength Cr-Si sintered body can be obtained by using a rapidly cooled alloy powder such as a gas atomized powder, and thus completed the present invention.
[0008] That is, the aspects of the present invention are as follows. (1) A Cr-Si-based sintered body containing Cr (chromium) and silicon (Si), characterized in that the crystal structure determined by X-ray diffraction is composed of chromium silicide (CrSi2) and silicon (Si), the CrSi2 phase is present at 60 wt% or more in the bulk, the sintered body density is 95% or more, and the average grain size of the CrSi2 phase is 60 μm or less. (2) The Cr-Si sintered body according to (1), characterized in that the flexural strength is 100 MPa or more. (3) A Cr-Si sintered body according to (1) or (2), characterized in that the amount of oxygen in the bulk is 1 wt % or less. (4) A sputtering target comprising the Cr-Si sintered body according to any one of (1) to (3). (5) A method for producing a thin film, comprising sputtering using the sputtering target according to (4).
[0009] The present invention will be described in detail below.
[0010] The present invention is a Cr-Si-based sintered body containing Cr (chromium) and silicon (Si), characterized in that the crystal structure determined by X-ray diffraction is composed of chromium silicide (CrSi2) and silicon (Si), the CrSi2 phase is present at 60 wt% or more in the bulk, the sintered body density is 95% or more, and the average grain size of the CrSi2 phase is 60 μm or less.
[0011] The crystal phase of the Cr-Si sintered body of the present invention is characterized by being a system consisting of a chromium silicide (CrSi2) phase and a silicon (Si) phase by XRD. If the silicidation reaction does not proceed sufficiently and other silicide phases (Cr3Si, Cr5Si3, CrSi) and chromium (Cr) phases that should not exist in the composition are present locally, microcracks are present due to density differences, and the sintered body is easily broken, especially in a large sintered body, and the sintered body cannot be manufactured with a good yield. In addition, when such a sintered body is used and high power is applied in sputtering, cracks are easily generated during discharge, which is undesirable as it causes a decrease in productivity in the film formation process.
[0012] The Cr-Si sintered body of the present invention is characterized in that the CrSi2 phase is present in the bulk at 60 wt% or more, preferably 70 wt% or more, and particularly preferably 80 wt% or more.
[0013] The sintered density of the Cr-Si sintered body of the present invention is characterized by being 95% or more in relative density. If the sintered density is lower than 95%, the strength decreases. Furthermore, when used as a sputtering target, the frequency of arcing increases, so the relative density is preferably 97% or more, more preferably 98% or more.
[0014] The grain size of the chromium silicide in the Cr-Si sintered body of the present invention is 60 μm or less. If the grain size exceeds 60 μm, the strength decreases rapidly. To obtain a stable high strength, the grain size is preferably 1 to 60 μm, more preferably 1 to 20 μm, and particularly preferably 1 to 10 μm.
[0015] The amount of oxygen in the bulk of the Cr-Si sintered body of the present invention is preferably 1 wt% or less, more preferably 0.5 wt% or less, further preferably 0.1 wt% or less, and even more preferably 0.05 wt% or less, from the viewpoints of particle generation when formed into a film and the yield of the film-based product.
[0016] The flexural strength of the Cr-Si sintered body of the present invention is preferably 100 MPa or more, more preferably 100 to 500 MPa, even more preferably 150 to 500 MPa, and particularly preferably 200 to 500 MPa. If the strength of the sintered body is high, cracks are unlikely to occur even during grinding and bonding processes, and the yield is high, resulting in good productivity. Furthermore, even when high power is applied during sputtering, cracks are unlikely to occur.
[0017] The Cr-Si sintered body of the present invention may contain unavoidable metal impurities other than Cr (chromium) and silicon (Si) in a total amount of 1 wt% or less, preferably 0.5 wt% or less, more preferably 0.05 wt% or less, and even more preferably 0.01 wt% or less.
[0018] As unavoidable metal impurities other than Cr (chromium) and silicon (Si), in particular Fe, Ni, Al, Mn, Cu and other metal impurities may be contained in a total amount of 1 wt% or less, preferably 0.5 wt% or less, more preferably 0.05 wt% or less, and even more preferably 0.01 wt% or less.
[0019] As for the individual elements, Fe may be contained in an amount of 0.1 wt% or less, preferably 0.05 wt% or less, and more preferably 0.01 wt% or less. Ni may be contained in an amount of 0.01 wt% or less, preferably 0.005 wt% or less, and more preferably 0.001 wt% or less. Al may be contained in an amount of 0.1 wt% or less, preferably 0.05 wt% or less, and more preferably 0.01 wt% or less. Mn may be contained in an amount of 0.005 wt% or less, preferably 0.001 wt% or less, and more preferably 0.005 wt% or less. Cu may be contained in an amount of 0.01 wt% or less, preferably 0.005 wt% or less, and more preferably 0.001 wt% or less.
[0020] Next, the method for producing the Cr-Si sintered body of the present invention will be described.
[0021] The method for producing the Cr-Si sintered body of the present invention includes steps including (1) an alloy raw material preparation step in which chromium and silicon are used by a gas atomization method, an arc melting method or the like, and (2) a sintering step in which the obtained raw material powder is sintered in a pressure sintering furnace such as a hot press furnace at a pressure of 50 MPa or less and a sintering temperature of 1100°C to 1300°C.
[0022] Hereinafter, each step of the method for producing a Cr-Si sintered body of the present invention will be described.
[0023] (1) Alloy raw material preparation process The raw materials used are chromium and silicon. The purity of the raw materials is preferably 99.9% or more, and more preferably 99.99% or more. If the raw materials contain a large amount of impurities, this can cause abnormal grain growth during the firing process and can be a source of particle generation during film formation. Also, raw materials with a low oxygen content are preferable. If the raw materials contain a large amount of oxygen, the final sputtering target will contain a large amount of oxygen, which can cause particle generation.
[0024] The synthetic raw material powder can be produced by a gas atomizing method or an arc melting method.
[0025] It is preferable to rapidly cool the alloy raw powder by a method such as gas atomization to produce a powder with a fine structure. In particular, the particles produced by the gas atomization method are spherical in size to the order of several tens of μm, and the powder has fine CrSi2 and Si phases within the spheres. Because of the small surface area and fine grains, the sintered body after firing can be low in oxygen and high in strength. A high-strength bulk can be produced by mixing fine powders, but the amount of oxygen will be high. Conversely, low oxygen can be produced by mixing coarse grains, but the strength will be low. Other methods of producing raw materials include rapid cooling methods such as quenched ribbon and arc melting.
[0026] The conditions for the gas atomization method are preferably melting temperature +50 to 300°C. More preferably, it is +100 to 250°C. Here, the melting temperature refers to the temperature at which the raw material powder melts, and is usually 1300 to 1500°C. If the difference from the melting temperature is small, the crystal phase with the higher melting point of the two phases precipitates first, making it difficult to refine the particles. On the other hand, if the difference from the melting temperature is large, the particles sinter together after atomization and adhere to the wall surface, resulting in a poor powder recovery rate.
[0027] In addition, it is preferable to store the powder after gas atomization in a vacuum or in an inert atmosphere of nitrogen, argon, etc. If the powder is left in the air, oxidation will occur from the surface, and the amount of oxygen in the powder will increase.
[0028] The arc power is an important condition for the arc melting method. This determines whether materials with large differences in melting points can be alloyed. For example, in the case of chromium and silicon, the melting point of chromium is 1863°C and that of silicon is 1414°C, so the melting power must be 50 to 200A. If the arc current is too high, the amount of chromium sublimated increases, so the arc melting power should preferably be in the range of 50 to 150A.
[0029] (2) Firing process The powder thus obtained is then preferably sintered in a pressure furnace such as a hot press furnace, since it is difficult to densify the powder in a non-pressure furnace due to the low diffusion coefficient of silicon.
[0030] The hot press pressure during sintering is preferably 50 MPa or less. If the pressure exceeds 50 MPa, it is difficult to prepare a hot press mold capable of applying pressure. When producing a large sintered body, the hot press pressure is preferably 5 to 50 MPa, more preferably 5 to 20 MPa, and particularly preferably 5 to 10 MPa.
[0031] The firing temperature is 1100° C. to 1300° C. If the temperature is less than 1100° C., the density does not increase sufficiently, and if the temperature exceeds 1300° C., the material may melt depending on the pressure of the hot press. The cooling rate is not particularly limited, and can be appropriately determined in consideration of the capacity of the sintering furnace, the size and shape of the sintered body, and the fragility of the sintered body.
[0032] The holding time during firing should be within 1 to 5 hours. If it is shorter than 1 hour, uneven temperatures will occur in the furnace and hot press mold, making it difficult to obtain a uniform structure. Conversely, if the holding time is long, productivity will decrease.
[0033] The atmosphere during firing is not particularly limited, but a vacuum or an inert atmosphere such as argon is preferable.
[0034] The Cr-Si sintered body of the present invention can be ground into a plate shape using a machining machine such as a surface grinder, a cylindrical grinder, a lathe, a cutting machine, or a machining center.
[0035] The Cr-Si sintered body of the present invention can be made into a sputtering target made of the Cr-Si sintered body of the present invention. As a method for producing a sputtering target, the sputtering target can be obtained by bonding to a backing plate or backing tube made of oxygen-free copper, titanium, or the like as necessary using indium solder or the like.
[0036] Moreover, a thin film can be produced by sputtering using the obtained sputtering target. Effect of the Invention
[0037] The Cr-Si sintered body of the present invention has high strength, and when used as a sputtering target, it is free from cracks even under high output, making it possible to obtain high productivity. Furthermore, since it preferably contains a small amount of oxygen, it is possible to reduce particles during film formation. [Brief description of the drawings]
[0038] [Figure 1] X-ray analysis diagrams of Example 1 and Comparative Example 3 EXAMPLES
[0039] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. The measurements in the examples were carried out as follows. (1) Density of sintered body The relative density of the sintered body is measured by the Archimedes method in accordance with JIS R 1634. The relative density was calculated by dividing the density by the true density. The weights of a [g] and Si phase are b [g] and their true densities are 4.98 [g / cm 3 ], 2.3 [g / cm 3 ] was used to calculate the arithmetic mean expressed by the following formula. d=(a+b) / ((a / 4.98)+(b / 2.3) (2) X-ray diffraction test The X-ray diffraction pattern of the mirror-polished sintered sample was measured in the range of 2θ=20 to 70°.
[0040] Scanning method: Step scan method (FT method) X-ray source:CuKα Power: 40kV, 40mA Step width: 0.01° (3) Sintered particle size The sintered compacts were polished to a mirror finish, observed under a scanning electron microscope, and the grain size of the sintered compacts was measured from the obtained sintered compact structure image by the diameter method. At least three random points were observed, and more than 300 grains were measured. (Scanning electron microscope observation conditions) Accelerating voltage: 10kV (4) Transverse bending strength Measurements were performed in accordance with JIS R 1601. (Measurement conditions for flexural strength) Test method: Three-point bending test Distance between fulcrums: 30mm Sample size: 3×4×40mm Head speed: 0.5mm / min. (5) Analysis of oxygen content After grinding 1 mm or more from the surface of the sintered body after firing, a sample was cut out from any part and the analytical values were used as the measurement data.
[0041] Measurement method: Impulse furnace melting - infrared absorption method Equipment: LECO TC436 Oxygen and Nitrogen Analyzer (6) Analysis of metal impurities After grinding 1 mm or more from the surface of the sintered body after firing, a sample was cut out from any part and the analytical values were used as the measurement data.
[0042] Measurement method: Glow discharge mass spectrometry (GDMS) Example 1 Cr flakes (4N): 42wt% and Si flakes (5N): 58wt% were melted in a carbon crucible, and powder was produced by gas atomization at a melting temperature of 1650°C. The powder was sieved (sieve size: 300μm) in air to adjust the particle size of the powder.
[0043] Next, this powder was placed in a carbon mold (53 mmφ) and sintered by a hot press method to obtain a sintered body. (Firing conditions) Firing furnace: Hot press furnace Heating rate: 200℃ / hour Heating atmosphere: vacuum reduced pressure atmosphere Firing temperature: 1250℃ Pressure: 10MPa Baking time: 3 hours A sintered body with a size of 53mmΦ×7mmt and no microcracks was obtained. The properties of the sintered body are shown in Table 1.
[0044] (Examples 2 to 5) Except for changing the firing conditions, a sintered body was produced in the same manner as in Example 1. The properties of the sintered body are shown in Table 1.
[0045] Example 6 Cr flakes (4N): 29 wt% and Si flakes (5N): 71 wt% were melted by an arc melting method under the condition of an output of 100 A. The obtained bulk was pulverized in a mortar and sintered under the conditions of Example 3. The properties of the sintered body are shown in Table 1.
[0046] Example 7 Cr flakes (4N): 42 wt% and Si flakes (5N): 58 wt% were melted in a carbon crucible, and the melting temperature was set to 1650°C. Powder was produced by gas atomization, and the particle size of the powder was adjusted using a sieve (sieve size: 300 μm) in a glove box (oxygen concentration: 0.1 wt% or less).
[0047] Next, this powder was placed in a carbon mold (53 mmφ) and sintered by a hot press method to obtain a sintered body. (Firing conditions) Firing furnace: Hot press furnace Heating rate: 200℃ / hour Heating atmosphere: vacuum reduced pressure atmosphere Firing temperature: 1200℃ Pressure: 20MPa Baking time: 3 hours A sintered body with a size of 53mmΦ×7mmt and no microcracks was obtained. The properties of the sintered body are shown in Table 1.
[0048] In addition, the amount of metallic impurities was analyzed by GDMS, and the total amount of metallic impurities other than Cr and Si was 0.034 wt% or less, and the amounts of individual impurities were as follows: Fe 0.0066 wt%, Ni 0.00082 wt%, Al 0.000048 wt%, Mn 0.00011 wt%, and Cu 0.000051 wt%. Example 8 29 wt% Cr flakes (4N) and 71 wt% Si flakes (5N) were melted in a carbon crucible, and the melting temperature was set to 1540°C. Powder was produced by gas atomization, and the particle size of the powder was adjusted using a sieve (sieve size: 300 μm) in a glove box (oxygen concentration: 0.1 wt% or less).
[0049] Next, this powder was placed in a carbon mold (53 mmφ) and sintered by a hot press method to obtain a sintered body. (Firing conditions) Firing furnace: Hot press furnace Heating rate: 200℃ / hour Heating atmosphere: vacuum reduced pressure atmosphere Firing temperature: 1200℃ Pressure: 20MPa Baking time: 3 hours A sintered body with a size of 53mmΦ×7mmt and no microcracks was obtained. The properties of the sintered body are shown in Table 1. Furthermore, GDMS analysis of the amount of metallic impurities revealed that the total amount of metallic impurities other than Cr and Si was less than 0.026wt%, and the amounts of individual impurities were Fe 0.0027wt%, Ni 0.00039wt%, Al 0.000022wt%, Mn 0.000041wt%, and Cu 0.000012wt%. Example 9 Except for changing the firing conditions, a sintered body was produced in the same manner as in Example 8. The properties of the sintered body are shown in Table 1. Example 10 Cr flakes (4N): 47 wt% and Si flakes (5N): 53 wt% were melted in a carbon crucible, and the melting temperature was set to 1540°C. Powder was produced by gas atomization, and the particle size of the powder was adjusted using a sieve (sieve size: 300 μm) in a glove box (oxygen concentration: 0.1 wt% or less).
[0050] Next, this powder was placed in a carbon mold (53 mmφ) and sintered by a hot press method to obtain a sintered body. (Firing conditions) Firing furnace: Hot press furnace Heating rate: 200℃ / hour Heating atmosphere: vacuum reduced pressure atmosphere Firing temperature: 1200℃ Pressure: 20MPa Baking time: 3 hours A sintered body with a size of 53mmΦ×7mmt and no microcracks was obtained. The properties of the sintered body are shown in Table 1. Furthermore, GDMS analysis of the amount of metallic impurities revealed that the total amount of metallic impurities other than Cr and Si was less than 0.03wt%, and the amounts of individual impurities were Fe 0.0062wt%, Ni 0.00078wt%, Al 0.000035wt%, Mn 0.000068wt%, and Cu 0.000041wt%.
[0051] Example 11 Except for changing the firing conditions, a sintered body was produced in the same manner as in Example 10. The properties of the sintered body are shown in Table 1. Comparative Example 1 Cr flakes (4N): 42wt% and Si flakes (5N): 58wt% were melted by the arc melting method. The properties of the bulk obtained after melting are shown in Table 1. Comparative Example 2 The bulk produced in Comparative Example 1 was pulverized in a mortar and then hot pressed to produce a sintered body. The properties of the sintered body are shown in Table 1. Comparative Example 3 Cr powder (45 μm) and Si powder (9 μm) were mixed by V-type mixing, and the mixed powder was hot pressed to produce a sintered body. The properties of the sintered body are shown in Table 1. Comparative Example 4 The powder produced by gas atomization was sintered under various sintering conditions. The properties of the sintered bodies are shown in Table 1. Comparative Example 5 Cr flakes (4N): 29wt% and Si flakes (5N): 71wt% were melted by the arc melting method. The properties of the bulk obtained after melting are shown in Table 1.
[0052] [Table 1]
Claims
1. The present invention relates to a Cr-Si sintered body that includes an alloy raw material preparation step of obtaining raw material powder by a gas atomization method using chromium and silicon, and a sintering step of hot-pressing the raw material powder at a pressure of 50 MPa or less and a sintering temperature of 1100°C to 1300°C. The sintered body includes Cr (chromium) and silicon (Si), and the crystal structure of the sintered body is determined by X-ray diffraction to be chromium silicide (CrSi 2 ), silicon (Si), and CrSi 2 The CrSi phase is present in the bulk at 60 wt % or more, the sintered body has a density of 95% or more, and 2 A method for producing a Cr-Si sintered body, characterized in that the average grain size of the phase is 60 μm or less.
2. 2. The method for producing a Cr-Si sintered body according to claim 1, wherein the firing step is performed for a firing time of 1 to 5 hours.
3. 3. The method for producing a Cr-Si sintered body according to claim 1, wherein the sintering step is performed in an inert atmosphere.
4. 3. The method for producing a Cr-Si sintered body according to claim 1, wherein the purity of chromium and silicon in said alloy raw material preparation step is 99.9% or more.
Citation Information
Patent Citations
Silicide film and semiconductor device using the same film
JP1996020863A
Metal silicide sputtering target and method for manufacturing the same
JP2003167324A
Silicide target manufacturing method
JP2004204278A
silicon-rich alloy
JP2013502368A
Si ALLOY POWDER FOR LITHIUM ION SECONDARY BATTERY NEGATIVE ELECTRODE ACTIVE MATERIAL AND METHOD FOR PRODUCING THE SAME
JP2014203768A